Handbook of research on reconceptualizing preservice teacher preparation in literacy education - Araujo, Dawn L.; Araujo, Juan Jose (IGI Global, 2022)
"This book provides relevant empirical research, case studies, and insights from university personnel about their experiences as they engage in redesigning undergraduate curriculum, teaching, and learning, helping those who want to improve their understanding of the key components of programs with a focus on literacy education